1997
DOI: 10.1084/jem.186.10.1663
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Autoimmune Diabetes in Monoclonal T Cell Nonobese Diabetic Mice

Abstract: It has been established that insulin-dependent diabetes mellitus (IDDM) in nonobese diabetic (NOD) mice results from a CD4+ and CD8+ T cell–dependent autoimmune process directed against the pancreatic beta cells. The precise roles that beta cell–reactive CD8+ and CD4+ T cells play in the disease process, however, remain ill defined. Here we have investigated whether naive beta cell–specific CD8+ and CD4+ T cells can spontaneously accumulate in pancreatic islets, differentiate into effector cells, and destroy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
393
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(408 citation statements)
references
References 54 publications
11
393
4
Order By: Relevance
“…Mice, bacteria and infection 8.3 NOD mice, expressing the rearranged T cell receptor genes of the diabetogenic CTL clone NY8.3, have been previously described [23] and were provided by P. Santamaria (University of Calgary, Calgary, AB, Canada). 8.3 NOD mice and NOD mice (Jackson Laboratory, Bar Harbor, ME, USA) were housed and bred under SPF conditions at the Child and Family Research Institute (Vancouver, BC, Canada), and used between 4 and 12 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice, bacteria and infection 8.3 NOD mice, expressing the rearranged T cell receptor genes of the diabetogenic CTL clone NY8.3, have been previously described [23] and were provided by P. Santamaria (University of Calgary, Calgary, AB, Canada). 8.3 NOD mice and NOD mice (Jackson Laboratory, Bar Harbor, ME, USA) were housed and bred under SPF conditions at the Child and Family Research Institute (Vancouver, BC, Canada), and used between 4 and 12 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…8.3 NOD CD8 + T cells recognise an immuno-dominant peptide from IGRP, termed IGRP 206-214 , a protein expressed by pancreatic beta cells, and these cells are representative of a significant fraction of CD8 + T cells in pancreatic islets at the onset of inflammation [23,28,29]. Adoptive transfer of IGRP-specific (islet antigen) CD8 + T cells [26] into infected NOD mice confirmed an increase in the proliferation and activation of these cells in the pancreatic LNs (Fig.…”
Section: Wt C Rodentium Infection Disrupts Intestinal Barrier Functimentioning
confidence: 99%
“…Starting with the pioneering work of Rammensee and colleagues [5,9], Kd has been widely studied, and Kd-specific immune responses described in a number of experimental systems. These include CD8 T cell responses: (1) against viral and bacterial pathogens [6,[19][20][21][22]; (2) in the NOD mouse model of diabetic autoimmunity [23][24][25][26][27]; and, (3), to tumor antigens [28][29][30][31]. Despite these many studies, the number of identified endogenously processed peptides selected by Kd is small.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, injection of an islet-specific CD4 + T cell clone was found to accelerate diabetes in young NOD mice [6]. Thus, a signal derived from CD4 + T cells seems to be required for efficient accumulation of autoreactive T cells in islets of Langerhans [7,8].…”
Section: Introductionmentioning
confidence: 99%